A descriptive-contrastive analysis of Chabacano and Tagalog noun reduplication patterns - Batausa, Corazon (De Castro) 1933- ([Quezon City s.n.], 1969)
This is a descriptive-contrastive analysis of Chabacano and Tagalog noun reduplication patterns in the objective of discovering the basic similarities and differences between reduplication patterns of the two languages in terms of form, meaning, and distribution.
Thesis (M.A.T.Pilipino)--University of the Philippines
Keywords: Chabacano dialect -- Word formation; Philippine languages -- Comparison; Tagalog language -- Word formation